Origen y transformación del conflicto ambiental: análisis de los procesos de participación y educación en dos estudios de caso. (2015)
This article is the result of a theoretical research applied with a case study methodology. Through socio-legal analysis are exposed two environmental conflicts: forestry of Forest Reserve of Blanco River and the construction project of the transfer of Guarino River to La Miel River, both in the department of Caldas, Colombia. The first part describes the origin and mutation of conflicts, triangulating the main theoretical, normative and legal points of reference with the facts and stages of disputes under study. The second part presents the participation and legal environmental education as transforming elements of the conflict. The findings show how the transformations of the two cases, aimed at the incidence of environmental legal education and participation to achieve access to justice and the redefinition of the scope of environmental struggles were understood.